2022
DOI: 10.1002/saj2.20375
|View full text |Cite
|
Sign up to set email alerts
|

Conservation practices induce tradeoffs in soil function: Observations from the northern Great Plains

Abstract: Over the past 30 years, agricultural land use in the northern Great Plains has negatively affected soil health and associated ecosystem services through grassland conversion to cropland and a transition away from small‐grain cropping systems to warm‐season crops. Mitigating these effects requires adoption of conservation practices, but information about how conservation practices influence on soil condition and function are needed. This study sought to quantify near‐surface soil responses to crop diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Dryland farming accounts for 60% of the total crop production, which plays a critical role in feeding the world's growing population [1,2]. Over 40% of the global dryland area is utilized as cropland, often characterized by limited water availability [1,2]. Other major challenges are poor soil quality due to low organic matter content, nutrients, and biological activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dryland farming accounts for 60% of the total crop production, which plays a critical role in feeding the world's growing population [1,2]. Over 40% of the global dryland area is utilized as cropland, often characterized by limited water availability [1,2]. Other major challenges are poor soil quality due to low organic matter content, nutrients, and biological activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Grassland restoration, with greater C sequestration potential and larger liable OC contents, may help improve soil quality more than forestland and cropland in this Mollisol region. Agricultural land use in the northern Great Plains of the United States has negatively affected soil health and associated ecosystem services through grassland conversion to cropland and a transition away from small‐grain cropping systems to warm‐season crops during the last 30 yr. Mitigating these effects requires the adoption of conservation practices. A study was carried out to quantify near‐surface soil responses to crop diversity and intensity, cover crops, livestock integration under controlled experimental conditions, and land uses (dryland cropping vs. perennial agroecosystems) on a common Haplustoll soil in south‐central North Dakota, USA (Liebig et al., 2022). They found that diverse and continuous cropping improved soil structure, nutrient supply potential, and biological habitat but increased soil acidification and soil NO 3 –N accumulation under dryland cropping practices in the northern Great Plains.…”
mentioning
confidence: 99%